Analisis Hadist tentang Hakikat Materi Pembelajaran, Karakteristik, dan Macam-Macamnya dalam Pendidikan Islam - Maslani Maslani; Mugeni Muhammad; Nur Sab’rina Fathimah; Wisnu Hambali Hidayat (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This article discusses hadiths related to the nature of learning materials, characteristics, and types in the context of Islamic education. In Islamic education, the learning materials taught by the Prophet Muhammad SAW include spiritual, intellectual, and social dimensions, which aim to form a complete individual (al-insan al-kamil). Through an analysis of various hadiths, this paper identifies the characteristics of learning materials that are comprehensive, morally oriented, and tailored to the needs of students. In addition, this paper also categorizes various types of learning materials, including aqidah, morals, worship, the Qur'an, and fiqh, which have an important role in forming the character and morals of students. Thus, this study confirms that understanding and implementing hadith-based educational materials can be a guideline in developing an Islamic education curriculum that is relevant and adaptive to the challenges of the times. The results of the study are expected to contribute to the development of better and more meaningful Islamic education for society.